Migration and Security in the EU: Reframing the Balance Between State Security and Human Security - KASMI , Walae (Revue Internationale du Chercheur, 2024)
Within the European Union (EU), migration has emerged as a central policy challenge, often framed as a security threat rather than a humanitarian issue. This article critically examines the EU’s migration policies, focusing on their prioritization of border control and deterrence over migrant well-being. Drawing on the concept of human security, the study critiques the current security-centric approach that often exposes migrants to human rights violations and unsafe conditions, as seen in the EU's agreements with Morocco, Libya, and Turkey. Using case studies from Spain's enclaves, the Canary Islands, and the Central Mediterranean route, the article highlights the human costs of restrictive migration policies. It advocates for a shift towards a human-centered migration framework that aligns with the EU’s humanitarian commitments and international obligations. Key recommendations include expanding safe migration pathways, fostering social inclusion, and ensuring accountability in external partnerships. By integrating human security principles, the EU can uphold its values while effectively managing migration in a sustainable and humane manner.